UNIFOR APPLICATION OF THE CARRIAGE BY AIR CONVENTIONS AND TREATY RULES OF CONSTRUCTION - Naboush, Dr. Eman (IJRDO - Journal of Social Science and Humanities Research, 2017)
Applying the carriage by air conventions requires interpreting their provisions and terms. There are several rules of interpretation. The most related rules are the Vienna rules and principles of treaty interpretation. Analysing the courts’ decisions regarding the carriage by air conventions show that these courts applied the Vienna rules in order to preserve the uniformity of application of air conventions. Most importantly, these rules were applied while interpreting the Warsaw Convention despite the fact that this Convention was enacted long time before the Vienna rules were adopted. The main reason is that the Vienna rules are merely codification to the preexisting international rules of interpretation. Since the carriage by air is performed in reliance on the carriage contract, the rules of interpretation of a contract were preserved also in the process of their interpretation. However, the rules of interpreting domestic statute are not preserved as they would affect the uniform application of the carriage by air conventions.